The Influence of Customer Requirement on the Development of Value Creation and the Implication on Customer Loyalty (A Study at Islamic Bank in Jakarta) - Finorita Fauzi (Journal of International Conference Proceedings, 2022)
The purpose of the study is to examine the effect of customer requirements and value creation on customer loyalty at Islamic Banks in Jakarta. This research was carried out based on a quantitative approach. Observations were made on a cross-sectional/one-shot time coverage, in 2022. Islamic Bank in Jakarta is the unit of analysis in this study, with the unit of observation is the customer of Islamic Bank in Jakarta. Causality analysis to answer the research objectives using PLS-SEM. This study took a sample of 100. The sampling technique used is stratified proportional random sampling. The test results support the hypothesis that customer requirements and value creation affect customer loyalty. This research produces managerial implications for the management of Islamic banks in Jakarta that to increase customer loyalty, it is necessary to develop value creation which is supported by a better understanding of customer requirements. Value creation needs to be prioritized on efforts to strengthen relationships with business partners.Keywords: bank, customer loyalty, Islamic bank, customer requirement, loyalty, value creation.